Evaluation of Loop-Mediated Isothermal Amplification Assay for the Detection of Pneumocystis jirovecii in Immunocompromised Patients. (19th November 2015) - Singh, Preeti; Singh, Sundeep; Mirdha, Bijay Ranjan; Guleria, Randeep; Agarwal, Sanjay Kumar; Mohan, Anant
Abstract : Pneumocystis pneumonia (PCP) is one of the common opportunistic infection among HIV and non-HIV immunocompromised patients. The lack of a rapid and specific diagnostic test necessitates a more reliable laboratory diagnostic test for PCP. In the present study, the loop-mediated isothermal amplification (LAMP) assay was evaluated for the detection of Pneumocystis jirovecii. 185 clinical respiratory samples, including both BALF and IS, were subjected to GMS staining, nested PCR, and LAMP assay. Of 185 respiratory samples, 12/185 (6.5%), 41/185 (22.2%), and 49/185 (26.5%) samples were positive by GMS staining, nested PCR, and LAMP assay, respectively. As compared to nested PCR, additional 8 samples were positive by LAMP assay and found to be statistically significant (p < 0.05 ) with the detection limit of 1 pg. Thus, the LAMP assay may serve as a better diagnostic tool for the detection of P. jirovecii with high sensitivity and specificity, less turn-around time, operational simplicity, single-step amplification, and immediate visual detection.